Gendered information channels for climate-smart agriculture practices: Evidence from India, Kenya, and Uganda - Welk, Lukas; Barooah, Prapti; Kato, Edward; Ndegwa, Michael K. (International Food Policy Research Institute, 2023)
Lack of access to information is an important barrier affecting women farmers’ adoption of climate-smart agri culture (CSA) practices and technologies. To overcome this barrier, the use of information and communication technologies is increasingly being promoted. However, digital tools might widen, rather than reduce, gendered information gaps given women’s lower use of mobile phones and mobile Internet as compared to men in sub Saharan African and South Asia. This policy note summarizes data on information channels that women and men farmers use for CSA practices in Gujarat, India, parts of Kenya, and central Uganda. The results can be used by governments, nongovernmental organizations, and other actor groups interested in ensuring equity in access to information on CSA practices in low- and middle-income countries.